Systematic review of clofazimine for the treatment of drug-resistant tuberculosis - Gopal, M. (2013)
The increased incidence of drug-resistant tuberculosis has created an urgent necessity for the development of new and effective anti-tuberculosis drugs and for alternative therapeutic regimens. Clofazimine (CFZ) is a fat-soluble riminophenazine dye used in the treatment of leprosy worldwide. CFZ has also been used as a Group 5 drug in the treatment of tuberculosis (TB). A large cohort study from Bangladesh published in 2010 described a treatment regimen for multidrug-resistant tuberculosis (MDR-TB) including CFZ as being highly effective against MDR-TB. We searched multiple databases for studies published through February 2012 that reported use of CFZ in MDR- and extensively drug-resistant TB (XDR-TB) treatment regimens. We identified nine observational studies (6 MDR-TB and 3 XDR-TB) including patients with drug-resistant TB treated with CFZ. Overall, 65% (95% confidence interval [95%CI] 54–76) of the patients experienced favorable outcomes, defined as either cure or treatment completion. Using random effects meta-analysis, 65% (95%CI 52–79) of those with MDR-TB and 66% (95%CI 42–89) of those with XDR-TB experienced favorable treatment outcomes. High-quality prospective cohort studies and clinical trials examining the effect of CFZ as part of drug-resistant TB treatment regimens are needed.